Green wave of change in the East Coast : PAS and anti-UMNO backlash in Kelantan - Azmil Tayeb (Penerbit Universiti Kebangsaan Malaysia, 2018)
This article aims to look at the surprisingly positive results of the Pan Malaysian Islamic Party (Parti Islam Se-Malaysia, PAS) in Malaysia’s recent 14th General Elections (GE14) and offers an analysis why the party had managed to defy the expectation of many pundits and polling agencies leading up to the GE14. While it is commonly agreed that most “opposition votes” in the GE14 were anti-UMNO votes, one is still at pains to explain why the “opposition votes” on the east coast of peninsular Malaysia overwhelmingly went to PAS and not its rival parties Amanah and Bersatu, unlike in other parts of the country. This article argues that in order to have a fuller understanding of the electoral “green wave” (referring to PAS’s color) that swept through the east coast region of the peninsular Malaysia we need to reach further back in history to trace and discern the root causes of “oppositional politics” that pervades this region, namely Kelantan. Deeply embedded historical injustices lodged within the collective social memory of the people of Kelantan help to define the kind of “oppositional politics” in the state. It can also explain why its people rather choose PAS than its rival parties when the former had almost no chance of taking over the federal government due to its decision to contest independently.